MENCERMATI FRASA NUMERALIA DALAM BAHASA JAWA (Observing Numerals Phrase in Javanese Language) - Dwi Sutana (SAWERIGADING, 2014)
The research described numerals phrase of Javanese language including number of elements, sequence pattern,and closeness hierarchy of interelements relationship. Method employed in the research was descriptiveentailing data collection, classification of data, and analysis of data. Technique of data collection was doneby writing down the sentences implying phrase in data card. In analyzing data, it was done by substitution,expansion, interruption, permutation, and paraphrase technique. Having been analyzed, it is then found thatmostly the head of numerals phrase placed in the left side and its interelement relationship was closed andcould not be permutated, whilst, the head placing the right side was in the contrary. Relating to the closedrelationship of interelements in numeral phrase, the closest modificator of the head was unit of number (forright side expansion) and aspect for the left.